TWO-YEAR RESULTS OF INTRAVITREAL INJECTIONS OF AFLIBERCEPT IN COATS DISEASE: A CASE REPORT. Issue Volume 16:Issues 4(2022) (July 2022) - Georgakopoulos, Constantinos D.; Tsapardoni, Foteini N.; Makri, Olga E.; Vavvas, Demetrios
Abstract : An 18-year-old man diagnosed with Stage 2B Coats disease was treated with aflibercept monotherapy consisting of 8 monthly, followed by 6 bimonthly, intravitreal injections of aflibercept over a period of 2 years. His visual acuity improved from 20/200 to 20/25 with significant decrease in retinal thickness and regression of macular edema and aneurysms. Abstract : Purpose: To report long-term results of treatment with intravitreal injections of aflibercept in a newly diagnosed case of Coats disease. Methods: An 18-year-old man presented to the retina clinic of our hospital complaining of blurred vision in the right eye for the past 3 months. His past medical and ocular history were unremarkable. The best-corrected visual acuity was 20/200 in the right eye and 20/20 in the left eye. Fundoscopy in the right eye revealed extensive macular edema with a circinate ring of hard exudates in the posterior pole temporally to the macula. Optical coherence tomography demonstrated macular edema with subretinal fluid. Peripheral telangiectasias and light bulb aneurysms in the inferior temporal arcade as well as in the nasal far periphery were found in the right eye in fluorescein angiography, confirming the diagnosis of stage 2B Coats disease. The left eye was normal. Results: The original therapeutic strategy proposed was antivascular endothelial growth factor injections in the right eye, followed by laser photocoagulation. However, the patient did not consent to laser treatment and was treated with aflibercept monotherapy with 8 monthly intravitreal injections of aflibercept, followed by 6 injections every 2 months for a total of 14 injections over a period of 2 years. The best-corrected visual acuity in the right eye improved to 20/25 while optical coherence tomography imaging revealed significant decrease in retinal thickness with resolution of macular edema, and fluorescein angiography demonstrated prominent regression of aneurysms and leakage. Conclusion: To the best of our knowledge, this is the first case treated with aflibercept monotherapy, suggesting the significant role of vascular endothelial growth factor in vascular permeability in Coats and supporting the rationale that antivascular endothelial growth factors are a valuable therapeutic option for Coats disease.